2012
DOI: 10.4102/sajip.v38i1.984
|View full text |Cite
|
Sign up to set email alerts
|

Depressed, not depressed or unsure: Prevalence and the relation to well-being across sectors in South Africa

Abstract: Orientation: Work engagement, burnout and stress-related ill health levels of individuals, suffering from depression, who are unsure whether or not they suffer from depression, or who do not suffer from depression, have not been investigated in South Africa.Research purpose: The main objectives of this study were to investigate the prevalence of depression amongst employees in South African organisations and the relationship of depression with specific well-being constructs.Motivation for the study: Organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Employees attributed this poor performance to significant problems in concentrating, as well as forgetfulness and indecisiveness. Furthermore, these depressed employees had significantly poorer interactions with colleagues, such as withdrawal and crying, underlying the serious emotional impact of depression on functionality [7]. Thus, the clear relationship between depression and presenteeism observed in this survey supports the vital need to improve employees' access to quality treatment (which will be discussed in more detail below).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Employees attributed this poor performance to significant problems in concentrating, as well as forgetfulness and indecisiveness. Furthermore, these depressed employees had significantly poorer interactions with colleagues, such as withdrawal and crying, underlying the serious emotional impact of depression on functionality [7]. Thus, the clear relationship between depression and presenteeism observed in this survey supports the vital need to improve employees' access to quality treatment (which will be discussed in more detail below).…”
Section: Discussionmentioning
confidence: 59%
“…A recent study observed that people who reported that they suffer from depression, as well as those who were unsure whether they suffered from depression, experience lower work engagement levels, higher burnout levels and more symptoms of stress-related ill health, than individuals who reported that they do not suffer from depression [7]. Furthermore, those who suffer from depression have 27 days out of role (defined as the inability to work or perform day-to-day activities at work) per annum [21][22][23].…”
Section: Depression Causes a Heavy Economic Burden In The Workplace Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Major depressive disorders is a risk factor for work disability 13 , especially in South Africa, where poverty 14 , stressful work conditions 3 and the advanced age of the work-force all contribute to a feeling of hopelessness 3,15 . The occupational therapist's experience of making return-to-work decisions is influenced by the employee being assessed, by the employers' requirements, and ultimately by the weight of making a decision that may have permanent consequences for the employee 16 .…”
Section: © Sa Journal Of Occupational Therapymentioning
confidence: 99%
“…These organisational changes also have an impact on individuals' jobs and could possibly influence workers' safety, health and well-being (Schaufeli & Bakker, 2004). Consequently, the once predictable and controlled work environment has become complex and unpredictable, impacting employees' energy and motivational levels, physical health and well-being (Bakker & Demerouti, 2007;French, Du Plessis & Scrooby, 2011;Nelson & Simmons, 2003;Rothmann & Jordan, 2006;Schaufeli & Bakker, 2004;Welthagen & Els, 2012).…”
Section: Introductionmentioning
confidence: 99%